2017
DOI: 10.1002/jrs.5092
|View full text |Cite
|
Sign up to set email alerts
|

Raman microspectroscopic studies of unirradiated homogeneous (U0.76Pu0.24)O2+x: the effects of Pu content, non‐stoichiometry, self‐radiation damage and secondary phases

Abstract: In this study, micro-Raman spectroscopy technique was implemented to characterize an unirradiated homogeneous Gigondas (U 0.76 Pu 0.24 )O 2+x sample, which had been stored for 30 years at room temperature under air. The impacts of Pu content, deviation from stoichiometry, self-radiation damage and formation of secondary phases were assessed by comparing the Raman spectra of the aged Gigondas with an annealed sample [(U 0.76 Pu 0.24 )O 2 ]. The Pu content of the sample was measured by electron probe microanalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 58 publications
(90 reference statements)
1
6
0
Order By: Relevance
“…This mode is originated from the M-O stretching, with M being coordinated in a cubic environment of eight oxygen atoms. The presence of forbidden modes in the Raman spectra of U 1−y Am y O 2±x oxides is not surprising; it has already been observed in various UO 2 [30][31][32][33] , U-Actinide 34 and Urare earth dioxides 11,13 , as a result of breaks in the translational symmetry, which can be induced by different factors, namely irradiation, doping, reduction or oxidation.…”
Section: Resultsmentioning
confidence: 92%
“…This mode is originated from the M-O stretching, with M being coordinated in a cubic environment of eight oxygen atoms. The presence of forbidden modes in the Raman spectra of U 1−y Am y O 2±x oxides is not surprising; it has already been observed in various UO 2 [30][31][32][33] , U-Actinide 34 and Urare earth dioxides 11,13 , as a result of breaks in the translational symmetry, which can be induced by different factors, namely irradiation, doping, reduction or oxidation.…”
Section: Resultsmentioning
confidence: 92%
“…Raman spectroscopy is an analytical tool that has been established in recent years as a reliable probe for this kind of studies, as confirmed by the large increase in the specialised literature . This is due to some of its features, as that (a) it does not require any special preparation of the sample, (b) the technique allows the analysis of a very small amount of sample, (c) it requires no direct contact between the experimental set‐up and the analyte, (d) it can be easily implemented (remote analysis, Raman probes, handheld systems, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, laser heating has been employed for analysing the oxidation behaviour and/or resistance of uranium‐based materials such as (U, Pu)O 2, (U, La)O 2, and even spent fuels . In these studies, oxidation of the samples to higher oxidation‐state phases has been observed by Raman spectroscopy, using the laser as a heat source.…”
Section: Introductionmentioning
confidence: 99%
“…Talip et al used Raman microspectroscopy to study unirradiated homogeneous (U 0.76 Pu 0.24 )O 2+x to assess the effects of Pu content, nonstoichiometry, self‐radiation damage, and secondary phases. In this study, micro‐Raman spectroscopy was used to characterize an unirradiated homogeneous Gigondas (U 0.76 Pu 0.24 )O 2+x sample, which had been stored for 30 years at room temperature under air The impacts of Pu content, deviation from stoichiometry, self‐radiation damage and formation of secondary phases were assessed by comparing the Raman spectra of the aged Gigondas with an annealed sample (U 0.76 Pu 0.24 )O 2 …”
Section: Solid State Studiesmentioning
confidence: 99%